2017
DOI: 10.1080/10826084.2016.1261899
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Adversities and Substance Misuse Among the Incarcerated: Implications for Treatment and Practice in Correctional Settings

Abstract: Background Incarcerated populations have high rates of childhood adversities and substance use problems. Moreover, childhood adversities are well-documented predictors of substance misuse. Objective To investigate the impact of childhood sexual and physical abuse, caregiver abuse of drugs or alcohol, and time spent in foster care on several substance misuse outcomes. Methods Data comes from a sample of 16,043 incarcerated men and women in the United States Survey of Inmates in State and Federal Facilities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 51 publications
5
24
1
3
Order By: Relevance
“…The finding that women experienced more childhood sexual abuse than men is also consistent with the literature among substance misusers and the general population (Greenfield et al, ; Heffner, Blom, & Anthenelli, ; Marotta, ; Rosen, Ouimette, Sheikh, Gregg, & Moos, ; Shand, Degenhardt, Slade, & Nelson, ; Simpson et al, ; Titus, Dennis, White, Scott, & Funk, ; Wellman, ). However, we did not find sex differences regarding emotional and physical abuse.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The finding that women experienced more childhood sexual abuse than men is also consistent with the literature among substance misusers and the general population (Greenfield et al, ; Heffner, Blom, & Anthenelli, ; Marotta, ; Rosen, Ouimette, Sheikh, Gregg, & Moos, ; Shand, Degenhardt, Slade, & Nelson, ; Simpson et al, ; Titus, Dennis, White, Scott, & Funk, ; Wellman, ). However, we did not find sex differences regarding emotional and physical abuse.…”
Section: Discussionsupporting
confidence: 81%
“…Studies of sex differences in the prevalence of childhood emotional and physical abuse among substance misusers and the general populations have reported mixed results. Some studies found that women experience more emotional and physical abuse (Christoffersen, Armour, Lasgaard, Andersen, & Elklit, ; Shand et al, ; Simpson et al, ; Titus et al, ), whereas others found that men experience more physical abuse (Kilpatrick & Saunders, ; Marotta, ; Rounds‐Bryant, Kristiansen, Fairbank, & Hubbard, ) or no sex differences in emotional and physical abuse (Greenfield et al, ; Heffner et al, ; Simpson et al, ). Whether or how childhood abuse may influence substance misuse differently in men and women remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the present study confirms the risk effect of CAs on SUDs and adds new evidence to support the role of the 5-HTTLPR polymorphism. Further studies and future meta-analyses focused on G×E interactions are needed to clarify these nature–nurture interactions as such findings might have important implications in the prevention and treatment of SUDs 75…”
Section: Discussionmentioning
confidence: 99%
“…Die meeste deelnemers dra nog die wonde van ongelukkige kinderjare. Soos aangetoon deur navorsers soos Marotta (2017) en Myers et al (2018), lei moeilike kinderjare dikwels tot Ɖ alkohol-en dwelmprobleem in Ɖ poging om onopgeloste trauma te hanteer. Op die mesovlak bied gemeenskappe dikwels nie ondersteuning aan kinders wat trauma ervaar nie, wat dan saamgedra word in die volwasse lewe.…”
Section: Probleemstellingunclassified
“…Myers et al (2018) se studie bevestig dat fisieke en seksuele trauma soos deur baie van die deelnemers beleef, Ɖ toename in alkohol-of dwelmmisbruik tot gevolg het, asook Ɖ groter blootstelling aan HIV. Marotta (2017) noem dat daar Ɖ korrelasie is tussen vroue wat in die tronk is (soos een deelnemer aangedui het), trauma in die kinderjare en die misbruik van alkohol of dwelms.…”
Section: Tema 2:teenspoed In Die Volwasse Leweunclassified